Political Culture of Transforming Countries: The Experience of China in the Past 40 Years since Reform and Opening Up - F. Haiting (Контуры глобальных трансформаций: политика, экономика, право, 2021)
Since the establishment of political culture analysis framework by Almond, it has become an important tool of political science and political analysis. The basic consensus on political culture is that a good political culture can promote political development. Many countries in transformation expect to shape their own civic culture as soon as possible to match their democratization process, but things often go against their wills. They are faced with a dilemma between traditional culture and civic culture at the very beginning of transformation. Besides, the development of political culture does not always present the simple path of traditional to modern type. Therefore, it is very necessary to reflect the principles of political culture development in combination with history and reality. From the view of Chinese scholars, political culture is neither only belief, feeling and attitude of individual, nor the ideology of a nation, but has multi-level content including ideology, value, psychology and action. This view combines the method of political culture analysis, the definition of Soviet culturology and the understanding of Chinese traditional culture. In transforming countries, the development of political culture is mainly manifested in the change and interaction of political subcultures. And at the same time, political subculture interacts with the change of social structure and political system. There are six main types of political subculture in transforming countries: political subculture of countryside and peasants, workers and migrant workers, private entrepreneurs, bureaucrats and officials, middle class and network. Through the analysis of these main types of political subculture in China after the reform and opening up, it can be concluded that political culture may present a complex path of development, and there may also be a variety of different development patterns and ideal forms.